Public versus Private Investment in Human Capital: Endogenous Growth and Income Inequality - Glomm, Gerhard; Ravikumar, B. (Journal of Political Economy, 1992)
In this paper, the authors present an overlapping generations model with heterogeneous agents in which human capital investment through formal schooling is the engine of growth. The authors use simple functional forms for preferences, technologies, and income distribution to highlight the distinction between economies with public education and those with private education. The authors find that income inequality declines more quickly under public education. On the other hand, private education yields greater per capita incomes unless the initial income inequality is sufficiently high. The authors also find that societies will choose public education if a majority of agents have incomes below average. Copyright 1992 by University of Chicago Press.